The Relationship between General Skills Training and Employees’ Turnover Intention - Ai, Zehua (2020)
Organizational Support Theory and Human Capital Theory hold different views on the role of general skills training in organizational management. This dissertation empirically examines the influence of participation in general skills training on turnover intentions. This study uses the Ordinary Least Squares and Maximum Likelihood Methods to analyze turnover intentions and the involvement in general skills training of 119 young Chinese workers. The results show that participating in general skills training reduces employee turnover. As predicted by Organizational Support Theory, participation in general skills training can indirectly influence employees’ turnover intentions through perceived organizational support and job satisfaction. This dissertation also finds that general skills training significantly affects young female employees' turnover intentions. These findings support Organizational Support Theory. Furthermore, this dissertation provides theoretical support for organizational management practices that include general skills training. However, this is a cross-sectional study, and the sample size is small, which creates limitations. Future research should collect more samples and consider the unique management context of Chinese organizations.